Association of the CHGA gene polymorphism in patients with hemorrhagic stroke and/or aneurysm - Joanilson C. M Santos Jr; Caroline F Fratelli; Alan Cristian F Nóbrega; Suzana Cristina Rodrigues; Ligia Canongia A. C Duarte; Calliandra Maria S Silva; Jonathan D Lima; Luzitano B Ferreira; Daniel O Freire; Vivian Taís F Cipriano; Izabel Cristina R Silva; Hélia Carla Souza (Sociedade Brasileira de Patologia Clínica, 2020)
ABSTRACT Introduction: Cerebrovascular diseases have been associated with several genes. Chromogranin A (CHGA) has been used as maker in cardiovascular disease. Therefore, evaluating the polymorphism and verifying its association with this pathology is very important to better understand this disease. Objective: The aim of this study was to identify the association between coding region polymorphism in -264 position of the CHGA gene (Glu264Asp) and hemorrhagic stroke (HS)/aneurysm in the Federal District, Brazil. Methods: This is a population-based case-control, involving 45 cases with HS and/or aneurysm. Polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP) method is used for genotyping these samples. A significance level of 5% was adopted. Results: The absence of the CC genotype the Glu264Asp CHGA polymorphism in the study participants and the significant presence of the GC heterozygote genotype were observed in this study. However, the distribution of genotypes did not differ statistically in the groups. Conclusion: The Glu264Asp CHGA polymorphism does not seem to contribute to the genesis of the CHGA protein expression in this patients group, but to understand whether or not there is a possible association of the pathology in question and whether the mutation will contribute in the gene therapy and thus to improve patients' quality of life.